2022
DOI: 10.47067/ramss.v5i2.219
|View full text |Cite
|
Sign up to set email alerts
|

Russia-Ukraine Crisis and Its Impact on South Asia

Abstract: On February 24, 2022, Russia invaded Ukraine under the pretense of national security. The Russia-Ukraine war is likely bound to give birth to severe issues including economic implications for the parties involved, and for the world’s atomic states. The imposition of serious sanctions on a petro-state such as Russia will have long lasting terminal effects, one of which could be the surge in global oil prices. The economic impact of Putin’s war on Ukraine is largely political when it comes to Russia. The economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…e results present the effect of the Russian-Ukrainian war on the construction industry that consists of the expectations of the research of Shah and Majeed [41] that stated that " is war will not only drive up the prices of raw materials, but it will also cause a shortage of exported goods, which will directly affect ordinary people. "…”
Section: Discussionmentioning
confidence: 99%
“…e results present the effect of the Russian-Ukrainian war on the construction industry that consists of the expectations of the research of Shah and Majeed [41] that stated that " is war will not only drive up the prices of raw materials, but it will also cause a shortage of exported goods, which will directly affect ordinary people. "…”
Section: Discussionmentioning
confidence: 99%
“…According to the regional analysis, the study confirmed the existence of a severe negative impact of the Russian-Ukrainian war on the economies of the countries from Asia and Europe. Shah et al (2022) argued that the sanctions placed on Russia by Western would cause interruptions in the supply of crude oil, natural gas and other exports by Russia. Ukraine's wheat and sunflower oil exports will be hampered to varying degrees depending on how much Russian airstrikes harm the country's infrastructure and agricultural land.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, we have also seen researches with more granularity in affected sectors, such as Izzeldin's, et al (2023) work on the war's impacts on global financial markets and Pandey and Kumar's (2023) study of the tourism sector stocks in particular. Geographically, researchers have also looked into the issue with focus on different locations including South Asia (Shah, et al 2022), Central Asia (Davis 2023) and the two warring states themselves (Khudaykulova, He and Khudaykulov 2022). This paper serves to fill a gap in literature with an encompassing review of the war's impact on the relatively more developed parts of Asia, including East Asia, Southeast Asia and South Asia, in regards to imminent shocks on key sectors and longer-term policy implications.…”
Section: Literature Reviewmentioning
confidence: 99%